Two-Faced: Roles of JNK Signalling During Tumourigenesis in the Drosophila Model - La Marca, John E.; Richardson, Helena E. (Frontiers in Cell and Developmental Biology, 2020)
The highly conserved c-Jun N-terminal Kinase (JNK) signalling pathway has many functions, regulating a diversity of processes: from cell movement during embryogenesis to the stress response of cells after environmental insults. Studies modelling cancer using the vinegar fly, Drosophila melanogaster, have identified both pro- and anti-tumourigenic roles for JNK signalling, depending on context. As a tumour suppressor, JNK signalling commonly is activated by conserved Tumour Necrosis Factor (TNF) signalling, which promotes the caspase-mediated death of tumourigenic cells. JNK pathway activation can also occur via actin cytoskeleton alterations, and after cellular damage inflicted by reactive oxygen species (ROS). Additionally, JNK signalling frequently acts in concert with Salvador-Warts-Hippo (SWH) signalling – either upstream of or parallel to this potent growth-suppressing pathway. As a tumour promoter, JNK signalling is co-opted by cells expressing activated Ras-MAPK signalling (among other pathways), and used to drive cell morphological changes, induce invasive behaviours, block differentiation, and enable persistent cell proliferation. Furthermore, JNK is capable of non-autonomous influences within tumour microenvironments by effecting the transcription of various cell growth- and proliferation-promoting molecules. In this review, we discuss these aspects of JNK signalling in Drosophila tumourigenesis models, and highlight recent publications that have expanded our knowledge of this powerful pathway.